Evaluating The Use of Paralegal Approach in Policy Advocacy - Ramaditya Rahardian; Rina Herlina Haryanti; Nadya Audina S Kurnia (Magister Administrasi Publik, 2018)
The purpose of this paper is to explore the approach adopted by workers’ organizations in Surakarta city to use paralegal services in an effort to change the formula used in calculating minimum wage in government regulation No. 78 / 2015. Data were collected using interview and documentation techniques. Data obtained in the field were analyzed using qualitative methods, that by understanding meaning of the phenomenon and making theoretical interpretation. Results of the research showed that advocacy to reject the formula used in calculating the minimum wage based on government regulation No.78/2015 using several ways that included influencing policy implementation, managing public opinion and creating space for a movement that opposes the policy. The study shows that workers who were strongly opposed to government regulation No.78/2015, used various policy advocacy channels to press their case, that included attempt to influence the implementation of the regulation, influence public opinion of the adverse impact of the regulation on worker wellbeing, and portraying the poor condition of workers’ welfare that requires government through actions that support higher wages rather than efforts that reduce their future incomes.